2015
DOI: 10.1371/journal.pone.0119905
|View full text |Cite
|
Sign up to set email alerts
|

Rarity-Weighted Richness: A Simple and Reliable Alternative to Integer Programming and Heuristic Algorithms for Minimum Set and Maximum Coverage Problems in Conservation Planning

Abstract: Here we report that prioritizing sites in order of rarity-weighted richness (RWR) is a simple, reliable way to identify sites that represent all species in the fewest number of sites (minimum set problem) or to identify sites that represent the largest number of species within a given number of sites (maximum coverage problem). We compared the number of species represented in sites prioritized by RWR to numbers of species represented in sites prioritized by the Zonation software package for 11 datasets in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 8 publications
(10 reference statements)
5
64
0
1
Order By: Relevance
“…Areas rich in endemic species with limited geographic distributions that are currently not well-represented in protected areas receive a higher value in our index than areas with few such species. Rarity-weighted richness values, such as the index we use here, perform well at identifying conservation priorities when compared with more complex conservation design algorithms (e.g., Zonation, [26]). …”
Section: Quantifying Conservation Valuementioning
confidence: 99%
“…Areas rich in endemic species with limited geographic distributions that are currently not well-represented in protected areas receive a higher value in our index than areas with few such species. Rarity-weighted richness values, such as the index we use here, perform well at identifying conservation priorities when compared with more complex conservation design algorithms (e.g., Zonation, [26]). …”
Section: Quantifying Conservation Valuementioning
confidence: 99%
“…But in cases where there are no clear biological grounds on which method is likely to be best, how should we determine what is most practical? The economic aspects associated with the contrasting methods were conventionally not considered by theory (Groeneveld 2005), yet adopting cost-effective approaches is fundamental to meet ambitious biodiversity targets with limited funding (McCarthy et al 2012) whether working on a fixed budget to capture as much biodiversity as possible (maximum coverage), or aiming to conserve a set amount of biodiversity for the minimum cost (minimum set) (Albuquerque and Beier 2015). Creating large sites could be more economical in terms of creation and management (Williams et al 2005) as they start to rely on natural processes (Lawton et al 2010) compared to managing smaller, individual sites.…”
Section: Bigger or More?mentioning
confidence: 99%
“…RWR ranks sites from 0 (all species can be represented without the site) to +∞ (the site is indispensable to the goal of representing all species). These ranks reflect complementarity, i.e., how well the accumulation of sites jointly represents common and rare species with a small number of sites [8]. Stein et al [7] used biogeographical patterns of RWR to identify hotspots of rarity-weighted richness (HRR) across the United States.…”
Section: Introductionmentioning
confidence: 99%
“…conserve imperiled species). Csuti et al [9] and Albuquerque & Beier [8] provided comparisons of RWR solutions to solutions produced by richness, linear programing and simulated annealing (one of the most effective algorithms to identify priority areas for conservation) and observed that RWR represented biodiversity almost as effectively as sites identified by linear programing, and was more effective than species richness and simulated annealing approaches. Albuquerque and Beier [8] also suggested that RWR is suitable for prioritizing large datasets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation